2015
DOI: 10.3389/fpls.2015.00691
|View full text |Cite
|
Sign up to set email alerts
|

A case study on the genetic origin of the high oleic acid trait through FAD2-1 DNA sequence variation in safflower (Carthamus tinctorius L.)

Abstract: The safflower (Carthamus tinctorius L.) is considered a strongly domesticated species with a long history of cultivation. The hybridization of safflower with its wild relatives has played an important role in the evolution of cultivars and is of particular interest with regards to their production of high quality edible oils. Original safflower varieties were all rich in linoleic acid, while varieties rich in oleic acid have risen to prominence in recent decades. The high oleic acid trait is controlled by a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Previous studies have shown that C. palaestinus and C. oxyacanthus are more closely related to cultivated safflower than C. lanatus and C. glaucus [23,24]. In the present study there was a positive correlation between relative content of saturated fatty acids and kinship among the five species.…”
Section: Fatty Acid Compositionsupporting
confidence: 69%
See 2 more Smart Citations
“…Previous studies have shown that C. palaestinus and C. oxyacanthus are more closely related to cultivated safflower than C. lanatus and C. glaucus [23,24]. In the present study there was a positive correlation between relative content of saturated fatty acids and kinship among the five species.…”
Section: Fatty Acid Compositionsupporting
confidence: 69%
“…This species is considered the nearest wild relative and also the progenitor of the cultivated safflower [22]. Introgression of some important genes including oil related ones from C. palaestinus to C. tinctorius is documented [23]. In this study similarity or even the superiority of some C. palaestinus genotypes in respect to oil content was observed when compared with that of C. tinctorius.…”
Section: Oil Contentmentioning
confidence: 60%
See 1 more Smart Citation
“…These features indicate that C. palaestinus is a good source of genes to improve C. tinctorius for these traits. Some researchers reported that C. palaestinus was genetically more closely related to cultivated safflower than to C. oxyacanthus (Majidi and Zadhoush, 2014; Rapson et al, 2015). The TO progenies had a higher number of branches per plant and lower plant height.…”
Section: Discussionmentioning
confidence: 99%
“…and C. oxyacanthus M. Bieb. species are the wild relatives of safflower (Ashri and Knowles, 1960; Majidi and Zadhoush, 2014; Ambreen et al, 2015; Rapson et al, 2015). Cultivated safflower is crossable with both its wild relatives to produce hybrid progenies (Ashri and Knowles, 1960).…”
mentioning
confidence: 99%